Novel circular single-stranded DNA viruses identified in marine invertebrates reveal high sequence diversity and consistent predicted intrinsic disorder patterns within putative structural proteins - Rosario, Karyna; Schenck, Ryan O.; Harbeitner, Rachel C.; Lawler, Stephanie N.; Breitbart, Mya (Frontiers in Microbiology, 2015)
Viral metagenomics has recently revealed the ubiquitous and diverse nature of single-stranded DNA (ssDNA) viruses that encode a conserved replication initiator protein (Rep) in the marine environment. Although eukaryotic circular Rep-encoding ssDNA (CRESS-DNA) viruses were originally thought to only infect plants and vertebrates, recent studies have identified these viruses in a number of invertebrates. To further explore CRESS-DNA viruses in the marine environment, this study surveyed CRESS-DNA viruses in various marine invertebrate species. A total of 27 novel CRESS-DNA genomes, with Reps that share less than 60.1% identity with previously reported viruses, were recovered from 21 invertebrate species, mainly crustaceans. Phylogenetic analysis based on the Rep revealed a novel clade of CRESS-DNA viruses that included approximately one third of the marine invertebrate associated viruses identified here and whose members may represent a novel family. Investigation of putative capsid proteins (Cap) encoded within the eukaryotic CRESS-DNA viral genomes from this study and those in GenBank demonstrated conserved patterns of predicted intrinsically disordered regions (IDRs), which can be used to complement similarity-based searches to identify divergent structural proteins within novel genomes. Overall, this study expands our knowledge of CRESS-DNA viruses associated with invertebrates and explores a new tool to evaluate divergent structural proteins encoded by these viruses.